2002
DOI: 10.1159/000056752
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imprinted Genes in Fetal Growth

Abstract: Genomic imprinting is the phenomenon by which one of the two alleles of a subset of genes is preferentially expressed according to its parental origin. This pattern of inheritance is different from the more frequent mode of Mendelian inheritance, which is not influenced by the parental origin of the allele. The idea that imprinted genes can affect fetal growth is becoming increasingly intriguing as it has been shown that most imprinted genes are expressed in the placenta and some play a role in regulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 74 publications
1
59
0
9
Order By: Relevance
“…IUGR is the most common feature, a phenotype shared among matUPD7, matUPD14, patUPD6q24 and matUPD20. The fetal growth disturbance in UPD carriers is consistent with the action of imprinted genes during fetal growth, as recently reviewed [7]. In murine models, most of the 60 recognized imprinted genes are expressed during fetal life and, in particular, in the placenta, in which they may regulate fetal demand and maternal supply of nutrients.…”
Section: Genomic Imprinting Defects and Iugrmentioning
confidence: 65%
“…IUGR is the most common feature, a phenotype shared among matUPD7, matUPD14, patUPD6q24 and matUPD20. The fetal growth disturbance in UPD carriers is consistent with the action of imprinted genes during fetal growth, as recently reviewed [7]. In murine models, most of the 60 recognized imprinted genes are expressed during fetal life and, in particular, in the placenta, in which they may regulate fetal demand and maternal supply of nutrients.…”
Section: Genomic Imprinting Defects and Iugrmentioning
confidence: 65%
“…Although the influence of paternal genes on normal development and function of the placenta in humans and mice is known (Jinno et al, 1995;Miozzo and Simoni, 2002;Isles and Holland, 2005;Wagschal and Feil, 2006), the association between paternal characteristics and placenta previa or placental abruption has received little attention. A retrospective cohort study analyzed the connection between these pregnancy complications and missing paternal demographic data (age and ethnicity either alone or combined) in birth certificates of 26 336 549 births using US linked birth/infant death data from 1995 through 2001 (Getahun et al, 2006).…”
Section: Placenta Previa and Placental Abruption During Pregnancymentioning
confidence: 99%
“…Imprinted genes may account for only a fraction of the genome (e.g. , 0.3% (Miozzo and Simoni, 2002)), but these affect early development strongly and may have a major impact on fertility (Fowden et al, 2006). , Gebert et al (2006 compared bovine oocyte to sperm DNA and reported on a differentially methylated region in the imprinted insulin-like growth factor 2 gene and this allows further work on gene-specific methylation patterns during pre-implantation development.…”
Section: Developing New Genomic Research Areasmentioning
confidence: 99%